1990
DOI: 10.1002/aja.1001870208
|View full text |Cite
|
Sign up to set email alerts
|

Variations in atrioventricular valve innervation in four species of mammals

Abstract: In this series of studies, the innervation patterns of whole-mount preparations of bicuspid and tricuspid valves were studied by light microscopy in the mouse, rat, guinea pig, and opossum. The acetylcholinesterase-positive networks of nerve fibers showed many similarities in the basic patterns of valve innervation in all of the species studied, but several interspecies variations were observed. The basal zone of the valve adjacent to the fibromuscular atrioventricular ring displayed the most dense plexus of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Our working hypothesis is that mechanoreceptors in the leaflet may monitor leaflet stretch and that leaflet sensory (afferent) nerves transmit this information for local reflex and/or central processing. Anterior leaflets are known to be richly innervated with sensory and motor nerves (1,19,20,36,(43)(44)(45) [adrenergic and cholinergic (6, 8 -10)], with unmyelinated axons (18) and thick myelinated fibers (8,18,29,(43)(44)(45) (which may serve as mechanoreceptors) coursing through the atrial subendocardial plexus. Leaflet contractile elements could thus be appropriately activated via motor nerves to maintain constant anterior MV leaflet shape and position immediately before and during valve closure over the wide range of LV operating pressures and volumes.…”
Section: Ivc (A) Ivr (B) Ivc (C) Ivr (D) Ivc (E) Ivr (F) Ivc (G) Ivr (H)mentioning
confidence: 99%
See 1 more Smart Citation
“…Our working hypothesis is that mechanoreceptors in the leaflet may monitor leaflet stretch and that leaflet sensory (afferent) nerves transmit this information for local reflex and/or central processing. Anterior leaflets are known to be richly innervated with sensory and motor nerves (1,19,20,36,(43)(44)(45) [adrenergic and cholinergic (6, 8 -10)], with unmyelinated axons (18) and thick myelinated fibers (8,18,29,(43)(44)(45) (which may serve as mechanoreceptors) coursing through the atrial subendocardial plexus. Leaflet contractile elements could thus be appropriately activated via motor nerves to maintain constant anterior MV leaflet shape and position immediately before and during valve closure over the wide range of LV operating pressures and volumes.…”
Section: Ivc (A) Ivr (B) Ivc (C) Ivr (D) Ivc (E) Ivr (F) Ivc (G) Ivr (H)mentioning
confidence: 99%
“…Black springs, collagen; red arrows, valvular interstitial cells; red interdigitating symbols, leaflet atrial muscle. (29)], annulus, leaflet, chordae, and papillary muscles (1,6,8,10,12,18,26,(43)(44)(45) to carry this stimulus from the aorticmitral continuity into the anterior leaflet. Within the anterior leaflet, however, no myoneural junctions are observed (18,39), the neuromuscular distance being Ͼ50 nm and filled with connective tissue (8,18); thus contractile myofibers in the leaflet are not directly innervated, and paracrine action is most consistent with our findings.…”
Section: Ivc (A) Ivr (B) Ivc (C) Ivr (D) Ivc (E) Ivr (F) Ivc (G) Ivr (H)mentioning
confidence: 99%
“…Although recent studies have reported PGP 9.5, TH, NPY, SP and CGRP-like immunoreactive nerves in the atrioventricular valves (Ahmed et al, 1997), the changes of peptidergic nerves in the atrioventricular valves of the diabetic rat have not been studied. The zones of the atrioventricular valves were termed as basal, intermediate and distal zones in previous studies (Williams et al, 1990;Jew et al, 1996;Ahmed et al, 1997;Jew and Williams, 1999). The changes of peptidergic nerves in the atrioventricular valves at 24 months post-diabetes was increased compare with that at 12 months post-diabetes.…”
Section: Discussionmentioning
confidence: 92%
“…This has been well documented in the human cardiac valves with age from 3 months to 21 years (Marron et al, 1996). The networks of the atrioventricular valves were termed as "primary plexus" and "secondary plexus" in previous studies (Williams et al, 1990 andAhmed et al, 1997). In the diabetic rat, there were less NPY-like immunoreactive nerve fibres in the atrioventricular valves and chordae tendinae.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation